Branched glycerol dialkyl glycerol tetraethers (brGDGTs) from a loess-paleosol sequence (Yuanbao) located at the western edge of the Chinese Loess Plateau over the past 130,000 years - Jingjing Guo; Louise Fuchs; Martin Ziegler; Youbin Sun; Francien Peterse (PANGAEA, 2024)
In this dataset, the loess proxies and branched glycerol dialkyl glycerol tetraethers (brGDGTs) from a loess-paleosol sequence (Yuanbao) located on the western edge of the Chinese Loess Plateau are included. In total, 872 loess and paleosol samples were investigated for loess proxies, and 580 samples were extracted for brGDGT records spanning the past 130,000 years. We reported 15 compounds of brGDGTs and three proxies based on the relative abundance of brGDGTs (i.e., methylation of 5-methyl brGDGTs, MBT extquotesingle5Me; isomer ratio, IR; degree of cyclization, DC). The estimated temperature above freezing months based on MBT extquotesingle5Me has also been reported using the Bayesian model.